2013
DOI: 10.1089/fpd.2012.1256
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxin-Encoding Genes inStaphylococcusspp. from Bulk Goat Milk

Abstract: Although Staphylococcus aureus has been implicated as the main Staphylococcus species causing human food poisoning, recent studies have shown that coagulase-negative Staphylococcus could also harbor enterotoxin-encoding genes. Such organisms are often present in goat milk and are the most important mastitis-causing agents. Therefore, this study aimed to investigate the occurrence of enterotoxin-encoding genes among coagulase-positive (CoPS) and coagulase-negative (CoNS) staphylococci isolated from raw goat mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
8
21
1
2
Order By: Relevance
“…In agreement with previous studies, we found that enterotoxigenic CM isolates mainly harbored the sec gene (Akineden et al 2008;Lyra et al 2013;Scherrer et al 2004). None of our CM isolates carried the seb gene.…”
Section: Detection Of Se and Tst Genessupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies, we found that enterotoxigenic CM isolates mainly harbored the sec gene (Akineden et al 2008;Lyra et al 2013;Scherrer et al 2004). None of our CM isolates carried the seb gene.…”
Section: Detection Of Se and Tst Genessupporting
confidence: 93%
“…The frequent combination of seg and sei genes in toxigenic S. aureus strains in our study is consistent with previous reports (Lyra et al 2013;Rosec and Gigaud 2002;Scherrer et al 2004). Some authors reported a predominant and systematic co-detection of seg and sei genes (Rosec and Gigaud 2002) whereas others have reported their presence individually or in different combinations with other se genes (Arcuri et al 2010;Cremonesi et al 2007;Zouharova and Rysanek 2008).…”
Section: Detection Of Se and Tst Genessupporting
confidence: 93%
See 1 more Smart Citation
“…Information about enterotoxin-encoding genes in Staphylococci from goat milk is scarce in Brazil. However, the frequency of positive isolates found in the present study is very similar to 23.3% of coagulase-positive staphylococci from bulk tank goat milk in Cariri region harboring at least one enterotoxin-encoding gene (Lyra et al 2013).…”
Section: Resultssupporting
confidence: 72%
“…This has also been reported as the most frequent gene in staphylococcus from goat milk by Scherrer et al (2004) and Lyra et al (2013), who observed secin 42% and 55.6% of positive staphylococci, respectively. The gene sec was also reported by Loncarevic et al (2005) as the most frequent classical enterotoxin-encoding gene amongst Staphylococcus from goat milk.…”
Section: Resultssupporting
confidence: 59%